Power amplifier for 5G systems - Belchior, Catarina Alexandra Xavier (2019)
In recent years, 5G systems have been in the spotlight and the discussion of how its requirements will change people’s lives is becoming increasingly more relevant. The fact that one of these requirements is to provide users with hundreds of MHz of available bandwidth, coupled with a scarce and crowded spectrum below 3GHz, has led to an increase in the operating frequency. Following this idea, this dissertation has the objective to design, implement and test a power amplifier for 5G systems, specifically for frequencies in the X band (8-12GHz). In this frequency band, the behaviour of RF components (capacitors) and other structures (via hole, substrate and connectors) have to be carefully analysed in order to better understand how these elements can affect the overall performance of the circuits. For this purpose several test circuits were designed, implemented and then, the simulated and measured results were compared. This initial step on the practical work allowed to make some updates on the simulation process and to draw other useful conclusions. After that, the design of a power amplifier for the X band was conceived. In order to reach the final objective, several intermediate prototypes were designed to make possible the identification and correction of potential error sources, for example in the matching networks and in the transistor model. In the end, a power amplifier for the frequency band of 9 to 9.6GHz, which means, 600MHz of bandwidth, was designed and implemented. The maximum drain efficiency achieved was 41-55% with a gain between 6-12dB. These results have proved to be competitive with the actual state-of-the-art. All design and simulation were performed using the Advanced Design System 2019 and Momentum software from Keysight Technologies.